Tradisional Wisdom Segati Village Community in Non-Timber Forest Product Utilization Sub-District Langgam District Pelalawan Riau Province - Rendra Mai Rizal; Defri Yoza; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Forest not only produce wood, but forests also produce non-timber forest products are utilized around the forest with a technique known or traditional way with traditional wisdom. The research was conducted in the Village District Segati Langgam Pelalawan starting from January to June 2013. The data collected was done by interview and direct observation in the field by using a sampling technique that Snowball Sampling and data collection techniques used were PRA (Participatory Rural Appraisal). Utilization of non-timber forest products that do Segati the village community on the use of honey, rattan, resin, tree branch, bamboo shoots, jackfruit, durian, kincung and medicinal plants. Utilization of non-timber forest products that use traditional wisdom found in the use of honey, resin, rattan, medicinal plants and tree branches. Traditional wisdom existing in society Segati village has a strategy in maintaining the wisdom which has been analyzed with SWOT analysis. One strategy is right that there needs to be a clear customary rules in the form of community activities especially in the utilization of non-timber forest products. Date were analyzed with descriptive qualitative analysis is used to determine the extent of the role of traditional wisdom in the community utilizing non-timber forest products and look at the phenomenon that has been happening in the field. The role of traditional wisdom to the preservation of non-timber forest products in village Segati seen with the customary rules which can provide a deterrent effect as well as to the public for fear of breaking all the traditional rules that apply such sanctions pengkafanan indigenous tree beehive and buffalo cuts.   Keywords: forest, non-timber forest products, traditional wisdom, SWOT analysis, analysis descriptive qualitative